Comparative evaluation of top papers outputs of OIC member countries in the Essential Science Indicators database - GhaviDel, Somayeh; Mostafavi, Ismael (Malaysian Journal of Library and Information Science, 2021)
The objective of this study was to analyze the top papers from Organization of Islamic Cooperation (OIC) member countries covered in the Essential Science Indicators (ESI) database during 2010-2019. The findings of the study showed that 41 out of 57 OIC member states have published 7,369 highly cited papers and 249 hot papers. The leading countries based on the overall top papers produced were Saudi Arabia, followed by Iran, Turkey, Malaysia, Pakistan and Egypt. Iran was ranked first in terms of hot papers. When analysed by document type, all of the top papers were articles and published in the English language. The Lancet ranks among the top in terms of publishing OIC member countries’ top papers, showing that it has a great academic influence producing highly cited papers and hot papers. The top five organizations producing top papers are all top universities in their country and they are also ranked globally. King Abdulaziz University contributed the most for both highly cited papers and hot papers. NANOFLUID was the most common keyword and core subject in highly cited papers, and the keyword MECHANICAL-PROPERTIES was the core subject identified in hot papers. Cluster 1 is the largest subject cluster of highly cited papers with the topic Nanotechnology and it is also the largest cluster of hot papers.